2009
DOI: 10.1103/physrevb.80.165207
|View full text |Cite
|
Sign up to set email alerts
|

Local redistribution of dopants and defects induced by annealing in polycrystalline compound semiconductors

Abstract: International audienceThe annealing of chlorine-doped polycrystalline CdTe films leads to the occurrence of an abnormal grain structure with the formation of both primary and secondary grains, the latter being larger and growing at the expense of the former. The spatial distribution of dopants and defects has been investigated within both types of grains by time-of-flight secondary-ion-mass spectroscopy imaging and spatially resolved cathodoluminescence. It is found that chlorine atoms similarly segregate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
7
1
Order By: Relevance
“…It is also assumed that concentration of cadmium vacancies is thereby not increased, as V Cd also accumulate at grain boundaries. 23 According to the calculation of Du, 24 the diffusion barrier for Cd vacancies (V Cd ) and Cu Cd is similar, 1.08 eV and 1.03 eV, respectively.…”
Section: Cu Solubility Limitation and Grain Boundary Segregationmentioning
confidence: 92%
“…It is also assumed that concentration of cadmium vacancies is thereby not increased, as V Cd also accumulate at grain boundaries. 23 According to the calculation of Du, 24 the diffusion barrier for Cd vacancies (V Cd ) and Cu Cd is similar, 1.08 eV and 1.03 eV, respectively.…”
Section: Cu Solubility Limitation and Grain Boundary Segregationmentioning
confidence: 92%
“…They can exist in various forms and play important roles in determining material properties, and thus have been one of the most active research topics in materials science [1][2][3][4][5][6]. For example, segregation of impurities to the GBs is an effective way to purify materials, thus improving material quality for device applications [7][8][9][10][11][12]. GBs also increase phonon scattering, allowing the thermoelectric properties of a material to be improved by intentionally controlling its GB size [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, work by Emazine et al showed an approximately 100× increase in the chlorine concentration throughout the CdTe material after a CdCl 2 treatment . Several studies have provided evidence that chlorine segregates at grain boundaries in CdTe: imaging via Auger emission spectroscopy (AES) , as well as limited time‐of‐flight SIMS (TOF‐SIMS) imaging of enhanced chlorine concentration at grain boundaries on the surface of the CdTe material . To the authors' knowledge, the works by Consonni are the only applications of TOF‐SIMS imaging (with a lateral resolution superior to AES and dynamic SIMS) examining the spatial distribution of chlorine in CdTe after the CdCl 2 treatment.…”
Section: Introductionmentioning
confidence: 99%